"Herbal seizures" – atypical symptoms after ibogaine intoxication: a case report. (December 2015) - Breuer, Lorenz; Kasper, Burkhard; Schwarze, Bernd; Gschossmann, Juergen; Kornhuber, Johannes; Müller, Helge
Abstract Introduction Misuse of various new psychotropic substances such as ibogaine is increasing rapidly. Knowledge of their negative side effects is sparse. Case presentation We present a case of intoxication with the herbal substance ibogaine in a 22-year-old white man. After taking a cumulative dose of 38 g (taken in two doses), he developed visual memories, nausea and vomiting. He developed a generalized tonic–clonic seizure with additional grand mal seizures. He was treated with midazolam and levetiracetam. Extended drug screenings and computed tomography and magnetic resonance imaging findings were all negative. Conclusions Knowledge of the side effects of ibogaine has mainly come from reports of cardiovascular complications; seizures are rarely mentioned and experimental findings are inconsistent. It seems that ibogaine acts like a proconvulsive drug at high doses.